POSSIBLE USE OF The Retropolation Method For Estimating Aggregated Indices On The Quarterly National Accounts - Hindls, Richard; Hronova, Stanislava; Marek, Lubos (European Scientific Journal, ESJ, 2016)
The effort to quickly establish reliable estimates for the values of the quarterly national accounts has led developed countries to attenuate direct statistical surveys as the primary data source in favour of modelling. A number of modelling methods utilise the relationship between an aggregated index on the national accounts and an index that is surveyed currently (quarterly or monthly). This paper presents assumptions and possibilities for the use of the retropolation method as one of the disaggregation methods.